KONTRIBUSI PEKERJA PEREMPUAN SEKTOR RUMPUT LAUT DI BLUTO KABUPATEN SUMENEP - Ariwidodo, Eko (STAIN PAMEKASAN, 2016)
Seaweed is one of the marine resources as capital for livelihood development in addition to the fishermen catch fish. Seaweed cultivation can support the survival of fishermen especially in Bluto Sumenep. Seaweed also can produce a wide variety of products that can provide benefits to the villagers. Seaweed farming activities is not only performed only by men, but women (or wives) can do as well. The purpose of this study is try to describe the characteristics of fishing seaweed; describe the division of labor between husband and wife fishing seaweed; analyze differences in access to and control over production resources between husband and wife; and the contribution of women to the household incomes of seaweed fishermen. The methods used quantitative method that is supported by qualitative method. The role and contribution of the wife can be seen from the amount of time devoted to each activity carried out both on productive activity, reproductive, and social activities. Wifes involvement in productive activities also contribute income to their household income. Wife revenues can contribute the household expenses when their husbands are still missing. Husband tends to play a role in productive activity, whereas the wife role in reproductive and social activities.